Bauran Promosi Wisata Edukatif Kebun Binatang di Instagram - Alifia Putri Farina; Anne Ratnasari (UNISBA Press, 2024)
Abstract. Tourism can contribute to the economic development of a country or region. In Indonesia, 90 percent of zoos are not up to standard, and several wildlife parks scattered across the country have reported mistreatment of animals. Lembang Park & Zoo is an educational tourist destination that combines the concept of an amusement park with a unique zoo. The aim of this research is to analyze the presentation of advertisements, the role of influencers, the role of Key Opinion Leaders, the presentation of events on Instagram, and the Bavarian-inspired concept to foster awareness of wildlife and nature at Lembang Park & Zoo. The research informants are the Marketing Division of Lembang Park & Zoo. The results of the research show that the presentation of advertisements includes bonuses presented on Instagram Ads, Call to Action (CTA) in the form of discounts, and partnerships. Influencers play a role in arousing curiosity and attracting customers at Lembang Park & Zoo. The role of Key Opinion Leaders provides credible information that can build trust among customers. The presentation of events at Lembang Park & Zoo includes the annual Lembang Park & Zoo event and weekly events directly related to animals. The Bavarian-style presented by Lembang Park & Zoo is considered unique and not boring, making customers comfortable to enjoy the atmosphere of Lembang Park & Zoo. The promotional mix conducted at Lembang Park & Zoo is deemed attractive and effective, as evidenced by the content disseminated on Lembang Park & Zoo's Instagram. Abstrak. Pariwisata mampu memberikan kontribusi terhadap pembangunan ekonomi suatu negara atau daerah. 90 persen wisata kebun binatang Indonesia tidak layak, beberapa taman margasatwa yang tersebar di Indonesia menemukan ada perlakuan semena-mena terhadap hewan. Lembang Park & Zoo merupakan tempat wisata edukasi yang memadukan konsep taman bermain dengan kebun binatang unik. Tujuan penelitian ini yaitu untuk menganalisis penyajian iklan, peraninfluencer, peran Key Opinion Leader, penyajian event yang terdapat di Instagram dan konsep ala Bavaria untukmenumbuhkan kepedulian terhadap satwa dan alam di Lembang Park & Zoo. Informan penelitian ini yaitu DivisiPemasaran Lembang Park & Zoo. Hasil penelitianmenunjukan bahwa penyajian iklan berupa bonus yang disajikan di Instagram Ads, Call to Action (CTA) berupadiskon, dan partnership. Peran Influencer di Lembang Park & Zoo dapat menumbuhkan rasa penasaran dan juga menarikperhatian pelanggan. Peran Key Opinion Leader memberikaninformasi yang kredibel sehingga dapat menumbuhkankepercayaan dari pelanggan. Penyajian Event di LembangPark & Zoo berupa event tahunan Lembang Park & Zoo dan event-event mingguan yang berhubungan langsung denganbinatang. Gaya ala Bavaria yang disajikan oleh Lembang Park & Zoo dinilai unik dan tidak membosankan sehinggamembuat pelanggan nyaman untuk menikmati suasanaLembang Park & Zoo. Bauran promosi yang dilakukandilakukan di Lembang Park & Zoo dikatakan menarik dan efektif, dapat dilihat dengan konten-konten yang disebarkan di Lembang Park & Zoo melalui Instagram.